The antiulcer and cytoprotective effect of ageratum conyzoides-honey combination in rats - Fathihah, B.; Mahmood, A.A.; Sidik, K.; Salmah, I. (Faculty of Medicine, University of Malaya, 2005)
Six groups of adult male Sprague Dawley rats, each consisting of six animals were used throughout the experiment. The gastroprotective effects of aqueous plant extract alone, honey alone or honey in combination with ethanolic or aqueous extracts of A. conyzoides and cimetidine were investigated in rats against ethanol-HClinduced gastric ulcer. Efficacy was assessed by determination of ulcer index and inhibition percentage. Oral administration of ethanol-HCl (5 ml kg-1 body weight) to fasted rats produced extensive lesions of gastric mucosa (Group 1). Pre-treatment with honey (2.5 g kg-1 body weight) alone (Group 2), aqueous plant extract alone (10% w/v 5 ml kg-1) (Group 3), or honey in combination with each of alcoholic extract (10% w/w 5 ml kg-1) (Group 4), aqueous extract (10% w/w 5 ml kg-1) (Group 5) or cimetidine (10 mg/ml honey 5 ml kg-1) (Group 6) orally 30 minutes before administration of absolute ethanol-HCl significantly (p < 0.05) protected gastric lesions by 46.74%, 61.50%, 76.68%, 78.39% and 56.55% respectively. Although the mechanism of gastric protection is unknown, honey in combination with each plant extract appears to increase the resistance of gastric mucosal cells to the necrotizing effect of strong irritants in the absolute ethanol-HCl mixture. The results suggest that honey in combination with each plant extract might be beneficial in the treatment of a variety of diseases in which gastric mucosal injury is present.